Carbon dioxide absorption into aqueous blends of monoethanolamine and glycerol in a packed bed column / Somayeh Mirzaei - Somayeh , Mirzaei (2018)
Absorption/stripping process using aqueous amine is a mature technology widely applied for removal of carbon dioxide (CO2) from natural gas, hydrogen, and other refinery gases, which makes it a suitable option to remove CO2 from flue gas in coalfired power plants. The most widely used amine for CO2 capture from coal fired power plants is monoethanolamine (MEA). The purpose of this work is to investigate glycerol as promoter with MEA solvent to enhance CO2 capture. Absorption/stripping process with MEA-glycerol blend presents an attractive option for CO2 capture from the gas mixture of CO2 and nitrogen (N2). Absorption process was simulated in Aspen Plus rate-based model using ENRTL-RK thermodynamic model with aqueous mixture of MEA-glycerol. The optimal concentration for CO2 removal was 10 wt% MEA-10wt% glycerol since, the CO2 removal efficiency increased from 62.24% for 10 wt% MEA aqueous solution to 64.33% for the mixture of 10 wt% MEA−10 wt% glycerol aqueous solution. Number of absorption/desorption runs (14 runs) were performed in the range of gas flow rate 1.4-3.9 L/min. CO2 loading analyses confirmed that CO2 rich loading increases as the gas flow rate rises since, the lowest and highest rich CO2 loadings for MEA system were 0.0365 and 0.126 mol CO2/mol MEA at 1.4 and 3.3 L/min, respectively. Moreover, the lowest and highest rich CO2 loadings increased to 0.0519 and 0.1446 mol CO2/mol alkalinity for MEA-glycerol system at same conditions. The results suggested that hybrid MEA-glycerol solution showed better CO2 absorption compared to aqueous MEA solution as glycerol increases the CO2 absorption capacity for MEA solvent. Five experimental absorption runs using MEA-glycerol solvent were modelled in Aspen Plus using RadFrac columns simulating both absorber and stripper conditions. The highest and lowest deviations between experimental and simulated rich CO2 loadings were 9.22% and 0.36% for gas flow rate 2.9 L/min and 1.7 L/min, respectively. Furthermore, with the increase of gas flow rate from 1.4 to 3.9 L/min, an increase in rich streams was observed from 29.46ºC to 30.14ºC and also reboiler heat duty rose from 98.14 MJ/h to 305.46 MJ/h. Therefore, Aspen Plus predicted the experimental data well, both for the absorber and desorber.